PENINGKATAN SIKAP ASERTIF MELALUI TEKNIK ASSERTIVE TRAINNING PADA SISWA DISABILITAS RUNGU DI SLB NEGERI 1 BANTUL - Faiz Noormiyanto dan Shinta Purwaningrum (Universitas PGRI Yogyakarta, 2019)
Â AbstrackThe purpose of this research is to increase assertive attitude with asertivve training technique to improve assertive attitude in students with disability. the development of assertiveness can be seen from how far the individual is able to actualize what he wants, express his personal opinion, have an attitude and get welfare for what his decisions. The type of research used is descriptive qualitative research. The subjects of the study were students with disabilities SDLB B SLB Negeri 1 Bantul Data collection using questionnaires, documentation and interviews. Data collection techniques used are interactive analysis of miles and hubberman. The results of this study indicate that the factual condition of assertive disability disability after experiencing the process of Assertive Trainning experienced a significant increase, which is marked by students with deaf disability able to respect the rights of self and others, dare to express opinions in public, at the time of learning as well as in the association, honest with ourselves and others, able to determine attitude by paying attention to the situation and conditions around, able to use body language in accordance with the feelings.Keywords: deaf, disability, assertive attitude, assertive training